Answer:
The true statement is that the expression is satisfied for n = -2.
Explanation:
Given:
![4n = (1)/(2)* (2n-12)](https://img.qammunity.org/2020/formulas/mathematics/high-school/18k81iy3daflg5l4n0oqn86b74nwpq1av4.png)
To check:
Left hand side = Right-hand side ( for n = -2)
Proof :
For n = -2
Consider Left hand side of the equation given above.
∴ Left hand side = 4n
= 4×(-2) ......................for n = -2
= -8
Consider Right-hand side of the equation given above
∴ Right-hand side =
![(1)/(2)* (2n-12)](https://img.qammunity.org/2020/formulas/mathematics/high-school/8b5vajw4xqcx9bnhkbqsqw4pteo2ifcdle.png)
![=(1)/(2)* (2*(-2) - 12) \\= (1)/(2)* (-4 - 12)\\ =(1)/(2)* (-16)\\ =-8](https://img.qammunity.org/2020/formulas/mathematics/high-school/6g6emubulc1ogitcx5swbf8p9n5vcsj406.png)
Now we get Left hand side equal to Right hand side
i.e. Left hand side = Right hand side
i.e.
is true for n = -2